Cat-transmitted disseminated cutaneous sporotrichosis caused by Sporothrix brasiliensis in a new endemic area: Case series in the northeast of Brazil - Valeriano, Carlos Alberto Tiburcio (2020)
Universidade Federal de Pernambuco. Programa de Pós-Graduação em Biologia Fúngica. Recife, PE, Brasil.